Key lessons in integrated landscape management in Ethiopia: Case study in Amhara Region - Adimassu, Zenebe; Engdayehu, Getachew; Tibebe, Degefie; Ayehu, Getachew Tesfaye; Abera, Wuletawu; Tamene, Lulseged (2024)
Efforts in landscape restoration over the past several years played significant role in in promoting multifunctional landscape restoration. Rich experiences, lessons and insights need to be consolidated to enhance landscape restoration strategies and options. Key lessons can be drawn from the various landscape restoration initiatives including community-based landscape management, learning landscapes led by research and academic institutions. In the evolution of integrated landscape management, innovative technical knowledge and methods have emerged through a learning by doing approach. However, these experiences and lessons are rarely documented or synthesized in a systematic and accessible manner. To date, only a few initial steps have been taken to document lessons learned. Much of this knowledge remains as tacit, collective, or individual understanding, retained within the memories of local resource users and community organizations. Where documentation does exist, it is often narrative-based and limited to areas where non-governmental organizations (NGOs), researchers, or resource management projects have been actively involved. Systematic documentation is crucial to effectively scale up innovative technological and methodological interventions for the rehabilitation of degraded landscapes landscape by capturing and sharing experiences, knowledge can be efficiently transferred as actionable lessons learned. Insights from innovative landscape interventions have significantly advanced technical, institutional, and knowledge management practices within participatory integrated landscape management initiatives. These lessons are vital not only for implementing integrated landscape management interventions on the ground, but also for informing and adapting regulatory and policy frameworks. As such they must be integrated into policy formulation and decision-making processes. This report briefly explains key lessons learnt from community-based integrated landscape management in the Amhara region and landscape the Ethiopian landscape restoration platform learning landscapes. The document provides an overview of selected innovative technical practices, approaches and lessons learnt in landscape management from the region and beyond. Please note that, only selective lessons are addressed in this document